Analisis Upaya Guru Pai Dalam Menumbuhkan Disiplin Ibadah Siswa SMK Negeri 1 Salatiga - Wahid Mustofa; Fathia Zahratun Nisa; Annisa Luthfiyyah Kaltsum; Septi Nur Kamilia; Maslikhah (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2026)
This descriptive qualitative research focuses on the efforts of the Islamic Religious Education (PAI) Teachers at SMK Negeri 1 Salatiga in fostering students' worship discipline through the strategies of habituation and role modeling. Data were analyzed using the Miles and Huberman interactive model, gathered from interviews, participatory observation, and documentation. The results indicate that the PAI Teachers implemented a comprehensive approach that encompassed eight routine programs. These programs include Morning Habituation (reciting Asmaul Husna), closely monitored Congregational Prayer (Dhuha, Dhuhur, Ashar), Tadarus Al-Qur'an, Weekly Infaq (alms), Kajian An-Nisa (for female students on their period), Jumat Taqwa (Pious Friday), Majlis Doa Mawar Allah (MDMA - Collective Prayer Assembly), and Kajian Masjid Al Ikhlas (for teaching staff). The synergy among PAI Teachers, homeroom teachers, and other educators supports these programs, focusing on establishing consistent routines and strengthening students' spiritual motivation. Despite facing challenges such as the tendency for worship to be formalistic, the consistency of habituation and teacher role modeling proved effective in building a structured religious culture. The study concludes that strengthening worship discipline requires a combination of planned school environmental control and internalization of values through the central role of the teacher as the primary exemplar.